Reinterpretation of the Meaning of Bait Al-Māl: Study of the Compilation of Islamic Law Articles 191 and 171 Letter I - Songgirin, Amin (Sinergi International Journal of Law, 2023)
This research discusses the reinterpretation of the meaning of the bait al-māl through a normative-descriptive method with several approaches, namely regulatory analysis, language and double movement theory (looking at the historical background-events and conditions of society), to be seen in the present context. The interpretation of the meaning of the bait al-māl actually places the role and function of the Prophet Muhammad SAW, both as an institution and manager, so that in the present context, the institution is an institution that manages and develops the assets of Muslims, the results are used for the benefit of meeting the basic needs of life and the welfare of the Muslim community. (especially the group of orphans, the poor, the neglected, many in debt due to the basic necessities of life, and ibn sabīl) and non-Muslims. In respect of inheritance for which there are no heirs, the management institution must understand that it represents the eternal nature of the property and the distribution of its benefits is intended only for the welfare of Muslims, as is the nature of inheritance.